VD_FINDINFO Jug / 2021 / 277 vom 15. Januar 2021 - VD Tribunal cantonal (2021)
ESCROQUERIE, ASTUCE, PLAIGNANT, PARTIE À LA PROCÉDURE, REJET DE LA DEMANDE, PREUVE ILLICITE | 146 CP, 118 CPP (CH), 141 CPP (CH)